PEMANFAATAN SISTEM PENUNJANG KEPUTUSAN DALAM MENENTUKAN KELAYAKAN AGROINDUSTRI JAMBU BIJI (PSIDIUM GUAJAVA LINN) BERBASIS MOBILE - Dhieka Avrilia Lantana (Universitas Nasional, 2020)
Guava is one of the horticultural fruit commodities which has a high economic value. With the potential of supporting natural resources, Indonesia has enormous prospects in developing guava. The great prospect of guava agro-industry in Indonesia means that entrepreneurs cannot simply invest capital in this sector, but a prospective product study and analysis must be carried out and an analysis of the amount of capital to be invested and the feasibility of the agro-industry business to be run so as not to suffer losses. Therefore, this study aims to determine the utilization of decision support systems in determining the feasibility of mobile-based guavava (psidium guajava linn) based on prospective product determination criteria according to Rachman (2011).